MICROBIAL ISOLATION AND PCR DETECTION OF TETRACYCLINE TYPE-(B) AND SULFONAMIDE (SUL1) RESISTANCE GENES IN BACTERIA ISOLATED FROM CLARIAS GARIEPINUS - OYELAKIN, O. O.; OLOYEDE, A. R.; AKINYEMI, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The study was carried out to isolate and identify the bacteria associated with different parts of Clarias gariepinus and to detect the presence of Tetracycline type B and Sulfonamide-resistant genes in the bacteria as well as determine their antibiotic susceptibility pattern. A total of 48 bacteria isolates from the skin, gill, and intestine of Clarias gariepinus were obtained and characterized microbiologically. The sensitivity test was determined using the Maxi disc high profile (-ve) diffusion method. Pure isolates were cultured in Nutrient broth for DNA extraction, DNA was extracted and PCR analysis was done using Tetracycline type B and Sulfonamide resistance gene primers. All the samples collected showed bacterial growth on Eosin methylene Blue (EMB) and Salmonella-Shigella Agar. Five different bacteria emerged from isolates obtained, namely Escherichia coli, Klebsiella oxytoca, Proteus spp., Salmonella spp, and Shigella spp. The Sensitivity test revealed that the five bacteria are sensitive to ciprofloxacin, pefloxacin, and tarivid. It was indicated that all the bacterial isolates were susceptible to Pefloxacin, Ciprofloxacin, and Tarivid. Escherichia coli were also susceptible to Chloramphenicol and Gentamycin. Escherichia coli was also resistance to Streptomycin, Augmentin and Amoxicillin. Shigella was susceptible to Septrin, Chloramphenicol, Sparfloxacin, Gentamycin, and Streptomycin. Shigella is also resistant to Amoxicillin and Augmentin. Samonella was also susceptible to Septrin, Chloraphenicol, Sparfloxacin, Gentamycin and Streptomycin. PCR analysis of Tetracycline type B and Sulfonamide resistance gene shows that the five bacteria isolates from different parts of the fish were resistant to the two antibiotics used, the five bacteria obtained have 700basepair, 400 basepair and 300basepair for Tetracycline type B and the size of Sulfonamide resistance gene was 400basepair. Therefore, the two antibiotics cannot be used to treat infection as a result of bacteria associated with Tetracycline type B and Sulfonamide